Effects of Autonomous Mobile Robots on Human Mental Workload and System Productivity in Smart Warehouses: A Preliminary Study. (December 2020) - Chen, Yuhao; Yang, Chizhao; Song, Bowen; Gonzalez, Nicholas; Gu, Yu; Hu, Boyi
Safety is of critical concern in human-robot collaboration. A human-in-the-loop experiment was conducted to assess the performance of the customized robot control scheme in a smart warehouse setting, where the human participants performed order picking and assembly tasks, and the mobile robot performed simulated pallet moving tasks. Three modes of human-robot interaction were tested (no robot involved, mobile robot with the empty payload and mobile robot with the full payload). Participants' pupillary response, subjective workload as well as task performance (completion time and errors) were recorded and compared between different modes. Preliminary results indicated a slight decrease in human productivity (completion time increased from 191.4 to 204.1 seconds, p = 0.041) was well compensated by the relatively large gain from the robotics outputs. Additionally, human mental workload was negatively impacted (pupil diameter increased from 4.0 to 4.2 mm, p = 0.012) by introducing the robot into the shared workplace.